Assessment of Coronary Artery Calcium on Low-Dose Coronary Computed Tomography Angiography With Iterative Reconstruction. Issue 2 (March 2016) - Braber, Thijs L.; Willemink, Martin J.; Bohté, Elzemiek H.; Mosterd, Arend; Leiner, Tim; Velthuis, Birgitta K.
Abstract : Objective: This study aims to evaluate whether coronary calcium scoring (CCS) is also feasible using low-radiation-dose coronary computed tomography angiography (CCTA) in combination with iterative reconstruction. Methods: Forty-three individuals without known coronary artery disease underwent both noncontrast CCS (±1 mSv) for reference Agatston scores and low-dose CCTA (±3 mSv). Raw CCTA data were reconstructed with filtered back projection (FBP), hybrid iterative reconstruction (HIR), and model-based iterative reconstruction (MIR). Calcification volumes were derived with thresholds of >351 and >600 Hounsfield units (HU) and converted to proxy Agatston scores with linear regression analysis. Results: Intraclass correlation coefficients for Agatston scores versus CCTA volumes with FBP and iterative reconstruction were excellent (ranges 0.94–0.99 and 0.96–0.99 for >351 HU and >600 HU thresholds, respectively). The >351 HU threshold resulted in higher CCTA volume scores ranging from 65.9 (15.1–347.0) for HIR to 94.8 (42.0–423.0) for MIR ( P = 0.001 and <0.001, respectively). The >600 HU threshold scores ranged from 14.1 (0.0–159.3) for HIR to 28.6 (0.0–215.6) for MIR ( P = 0.003 and 0.027, respectively). At >351 HU, reclassification occurred in 21 individuals (49%) for FBP and HIR and 25 individuals (58%) for MIR. Reclassifications decreased with >600 HU to 10 (HIR, 23%), 8 (FBP, 19%), and 4 (MIR, 9%). Conclusions: The CCS is feasible using iteratively reconstructed low-dose CCTA with a calcium threshold of >600 HU. Using MIR, only 9% of individuals were reclassified.